THE EFFORT OF INQUIRY APPROACH IN UPGRADING KNOWLEDGE OF FACT, CONCEPT, TENET AND SKILL OF INDONESIAN LANGUAGE - Achmad Suherman (STIBA IEC JAKARTA, 2020)
The purpose of this study is to analyze, how the upgrading of students’ knowledge concerning with the fact, concept, tenet and skil in processing of learning indonesian language through inquiry approach which is given by the teacher have the positive impacts. This reseach was done by qualitative descriptive with path method. The data collection has already been done through field observation, test,and documentation. The reseach subject was a teacher and a number of 40 students as an object There are comprehensively improving in fact, concept, tenet and skill students in a learning process of indonesian language through inquiry approach. The upgrading knowledge of students based on measuring cycles, namely: cycle I previous fact 37,5 % become 41,6 %. cycle II previous fact 41,6% become 62,5 %. III previous fact 62,5% become 91,6 % The upgrading knowledge of students on fact, concept, tenet and skil in a learning process of indonesian language through inquiry approach, based on measuring cycles have a positive significan impact where each of percentage cycles continously increase